Kriteria Guru Sekolah Minggu sebagai Gembala Anak Berdasarkan Yehezkiel 34:11-16 - Jessica Jessica; Yanto Paulus Hermanto; Tony Tedjo (Didache: Journal of Christian Education, 2021)
Sunday School ministry plays a pivotal role in introducing Jesus Christ as a Saviour to the children. As a children's pastor, Sunday School's teacher must have specific criteria to make the ministry grow even better. This research method is qualitative, followed by the descriptive analysis along with literature review toward the text in Ezekiel 34:11-16 "God, the True Shepherd (NKJV)." The study obtains three manners of God as a shepherd: God is gathering the scattered sheep, giving comforts to the sheep, and giving a proper rescue for each sheep. Leaning on those manners will lead the children's ministry in the church.